Les installations du quotidien Structures domestiques en Languedoc du Mésolithique à l'Âge du Bronze d'après l'étude des abris de Font-Juvénal et du Roc-de-Dourgne dans l'Aude - Gascó, Jean (Documents d'archéologie française, 1985)
In this paper, Jean Gascó (chargé de Recherche, Centre d'Anthropologie des Sociétés Rurales, E.R. 289 du C.N.R.S.) examines domestic structures which date from the Mesolithic, Neolithic and Bronze âge, excavated at the rock shelters of « Font-Juvénal » and « Roc-de-Dourgne » (Aude, France). Currently the study of such domestic structures is subject to detailed examination in France and has produced an abondance of material and elements to interpret concerning the typology, fonction, cultural data, evolution and typology of such structures. This research has lead to a typological approach of prehistoric domestic structures in Mediterranean Languedoc region and complements studies which have up to the moment concerned essentially the upper Paleolithic of northern France.